Psychoanalytic listening: Between unconscious and conscious - Limas Sutanto (Jurnal Psikiatri Surabaya, 2021)
Psychoanalytic listening can be deployed for enhancing the quality of clinical psychiatric practice. As a clinical skill, it should be teachable throughout the years of psychiatric residency. Nevertheless, the teaching of such important faculty is difficult due to the scarcity of a systematic, relatively structured model that can be used as an underpinning of learning that capability. This article is aimed at fulfilling a part of that lack of teaching methodology. The model offered in this article describes psychoanalytic listening as a mental process initiated by the therapist, which then goes through the patient too, which involves a continuing oscillation of unconscious apprehension and conscious comprehension. This rhythmic proceeding of affectively experiencing and rationally considering will expectedly bring about a mutual understanding between patient and therapist which then facilitates further clinical enterprises.